Bush v. Gore the court cases and the commentary (Brookings Institution Press, 2001)
"In the first half of this volume gathers what we and the editors at the Brookings Institution Press believe to be the most important legal documents in the Bush-Gore confrontation ... The book begins with the early advisory rulings on the recounts by Florida state officials. It moves on to the intermediate court rulings and ends with the critical decisions in early December by the Florida Supreme Court and the United States Supreme Court. We have included the dissents in all the major cases ... The second half of the book consists of contemporaneous commentaries on the controversy. These include columns, mazagine articles, editorials and also a few news stories that shed important light on the issues at stake"--P. 2.